Reaksi Pasar Modal terhadap Kenaikan Suku Bunga Acuan oleh The Fed tanggal 16 Juni 2022 - Merta, I Putu Evan Aditya Dharma; Putra, I Nyoman Wijana Asmara (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The research aims to examine whether the Indonesian capital market reacts to the increase in benchmark interest rates by The Fed on June 16, 2022. The event study method is used with an observation period of 107 days, where 100 days are the estimation period and 7 days are the event period. The research sample consists of companies listed in the LQ45 Index from February 2022 to July 2022. The sampling method used is purposive sampling. Market reactions are measured by Cumulative Abnormal Return (CAR) using the mean adjusted model. Data analysis is conducted using the one-sample t-test. The results indicate that there is no significant negative reaction in the Indonesian capital market regarding the increase in benchmark interest rates by The Fed.